Trataka: the Serene Consciousness - Sushmita; Anjali (International Research Journal of Ayurveda & Yoga, 2022)
Trataka is a Yogic practice, which means to gaze steadily. It is the practice of meditation that involves staring at a single point such as a small object, black dot or candle flame. It is primarily used to purify the mind and provides the strength to concentrate but it also improves eyesight and stimulus the brain via optic nerve. It acts as stepping stone between physically oriented practices and mental practices which lead to higher states of awareness. Trataka is explained in Shatkarma. Shatkarma is combination of six karmas of purification. The six types of karmas are: Dhauti, Basti, Neti, Trataka, Nauli and Kapala Bhati. Among those Shatkarma, Trataka destroys the eye diseases and removes sloth, etc. It is traditionally associated with Hath Yoga but it can also be used to achieve Raja Yoga. It forms a bridge between Hath Yoga and Raja Yoga. Yoga is a traditional method of meditation of ancient India which has explained about Shatkarma.